How to doodle everywhere : cute & easy drawings for notebooks, cards, gifts and so much more! - Kamo (Tuttle Publishing, 2020)
Your intrepid doodling guide Kamo is the author of many bestselling drawing guides, and in this one she shows you how to create simple doodles anywhere using just a ballpoint pen. You'll learn to use Kamo's motto: "Once you know the basics, you can draw anything!" This book provides hundreds of examples showing you how to create doodles that are lively and entertaining in three easy steps. Unlike fine-art or manga drawings, there are no rules and no fancy techniques. All that's needed is a free hand and a free spirit! This book makes an ideal gift for doodlers of all ages, beginners and amateurs alike. It shows you how to doodle anywhereu2014at home, in the office and on the gou2014on loose scraps of paper or in a notebook. Learn to use your decorative doodles to dress up and enliven things you use everydayu2014from letters, gift cards and invitations to journals, appointment books, household labels, business cards and scrapbooks.